Analisis Pengaruh Periklanan Mobile Terhadap Loyalitas Konsumen Kartu Prabayar XL Karawang - Windra Putra; Winarno Winarno; Rianita Puspa Sari (Jurnal Ilmiah Wahana Pendidikan, 2022)
The decline in the number of XL subscribers every year must be influenced by the many cellular operators that have sprung up, causing increased competition among cellular operators in attracting consumers to use their products. Creating customer loyalty can start with mobile advertising to tell the product. Good advertising will create, maintain satisfaction, and make loyal consumers. This study aims to determine the Effect of Mobile Advertising on Consumer Loyalty on XL Prepaid Cards (Survey of Users in Karawang). The population in this study were XL prepaid card users in Karawang. The sample set is 100 respondents using accidental sampling technique. The data collection method used is the method of distributing questionnaires. The data analysis technique used descriptive analysis and simple linear regression analysis. From the results of data processing simple linear regression analysis of mobile advertising with a value of 1.191 with a significant value of 0.00 and a t value of 12.623, it can be concluded that mobile advertising has an influence on consumer loyalty of XL prepaid card users in Karawang.